“IMAGE” ESSENCE OF EDUCATIONAL INSTITUTIONS AND IT`S ROLE IN PROMOTION IN A COMPETITIVE ENVIRONMENT (Multidisciplinary Journal of Science and Technology, 2024)
In this research paper investigated essence of the concept of image in various aspects, revealing the main approaches to its understanding. They reveal the criteria and components of its readiness to form an image, which indirectly affects the successful implementation of educational goals in modern conditions and the construction of the entire educational process.